Digital learning & retirement savings: a smarter future for Malaysians - Idris, Asma' Rashidah; Ali, Asiah; Zainal Abidin, Nurain Farahana; Mohd Zaid, Noor Azila; Zoolkefli, Zuliana; Kamarulzaman, Masrul Hayati; Sahrim, Noor Azila (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s digital age, retirement planning is no longer limited to paper statements and in-person consultations. Malaysians are increasingly turning to digital learning to boost their financial knowledge and ultimately, their savings. With easy access to online courses, mobile apps, and webinars, digital tools are transforming our preparation for our golden years. Retirement planning, once seen as a tedious and confusing process, is being reshaped through digital learning, making it more accessible, engaging, and personalised. From online courses and mobile applications to interactive webinars and social media communities, digital resources are helping Malaysians of all ages and backgrounds build financial literacy, understand longterm savings strategies, and make informed investment decisions. Whether it is a young professional just starting to save or a middle-aged entrepreneur planning for life after work, digital platforms offer the flexibility to learn at one's own pace, on any device, from anywhere (Selvadurai et al., 2018). This shift is not just about convenience, but also about empowerment. Malaysians are becoming increasingly proactive in managing their retirement savings, setting realistic goals, and utilising digital toolsthat offer real-time insights and personalised financial advice. As financial education becomes more democratised through technology, a smarter, more secure retirement is becoming a reality for many (Tiwari, 2024).